2013
DOI: 10.3109/13561820.2013.808611
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration may pay off: introducing a collaborative approach in an orthopaedic ward

Abstract: Fast-track hip and knee surgery focuses on optimising pain management, achieving early mobilisation and shortening the length of stay in hospital. These factors make interprofessional collaboration imperative. With the aim of further diminishing the length of stay for patients admitted to an orthopaedic ward for hip or knee replacement and with inspiration from an interprofessional training unit, a daily interprofessional meeting was introduced. At this interprofessional meeting, surgeons, nurses, occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…This proximity, combined with the shared responsibility for clients, supports previous research suggesting interprofessional placements can provide a 'safe place with space' (Hallin & Kiessling, 2016) and rich learning experiences for the students that break down barriers and strengthen interprofessional relationships (Falk, Hult, Hammar, Hopwood, & Dahlgren, 2013). Other studies have also found that both formal and informal interprofessional communication were essential to effective teamwork (Aase, Hansen, Aase, & Reeves, 2016), and can lead to improved client outcomes such as a reduction in hospital length of stay (Pape, Thiessen, Jakobsen, & Hansen, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…This proximity, combined with the shared responsibility for clients, supports previous research suggesting interprofessional placements can provide a 'safe place with space' (Hallin & Kiessling, 2016) and rich learning experiences for the students that break down barriers and strengthen interprofessional relationships (Falk, Hult, Hammar, Hopwood, & Dahlgren, 2013). Other studies have also found that both formal and informal interprofessional communication were essential to effective teamwork (Aase, Hansen, Aase, & Reeves, 2016), and can lead to improved client outcomes such as a reduction in hospital length of stay (Pape, Thiessen, Jakobsen, & Hansen, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…Systematic reviews have reported improvements in clinical outcomes, such as reduced mortality and hospital admissions (Holland et al, 2005), shortened hospitalization duration and reduced post-operative complications (Khan, Ng, Gonzalez, Hale, & Turner-Stokes, 2008;Pape, Thiessen, Jakobsen, & Hansen, 2013), and improved depression outcomes (Gilbody, Bower, Fletcher, Richards, & Sutton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The power imbalance became visible in cases requiring the administration of a contrast medium, especially when nurses were expected by radiographers and/or radiologists to perform these tasks in contravention of their scope of practice. These nurses were regarded as subordinate to other medical professionals in the department and they had very little professional autonomy compared to professional nurses outside the radiology department (Pape, Thiessen, Jakobsen, & Hansen, 2013).…”
Section: "They [The Radiographers] Have Just Called the Patient Insidmentioning
confidence: 99%